Radical-driven degradation mechanism of Cu(II)-EDTA during supercritical water gasification: Insights from ReaxFF molecular dynamics - Tingting Dai; Xiaoxia Guo; Ruochen Xiong; Weiqiang Liu; Weilong Yin; Weichong Deng; Wenwen Wei; Shi Liu; Wen Cao (Journal of Environmental Chemical Engineering, 2026)

An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

Soil salinity–driven sodium accumulation in alfalfa alters nutritional composition and feed quality in Northern China - Hunegnaw Abebe; Ruochen Yang; Xin Du; Zhenzhen Guo; Yan Tu (Animal Feed Science and Technology, 2026)

Research trends and hotspots of microalgae protein as a functional ingredient in plant-based foods: A bibliometric analysis based on the web of science - Jiayi He; Haoxie Xu; Keyu Lu; Chunli Guo; Ming Du; Ruochen Jia (Algal Research, 2026)

Community-level polycyclic aromatic hydrocarbon exposure and circulating microRNAs: Exploring their origins and regulatory functions in immune cells - Yufei Wang; Wending Li; Xuedan Xu; Yaxin Wang; Qin Jiang; Yutong You; Ruochen Yuan; Xiao Zhang; Yang Xiao; Chan Kong; Tingting Mo; Huan Guo; et al. (Journal of Hazardous Materials, 2025)

Study on supercritical water partial oxidation mechanism of sulfur-containing compounds by ReaxFF molecular dynamics - Ruochen Xiong; Guowei Xing; Yifeng Li; Zhiwei Ge; Liejin Guo (Journal of Hazardous Materials, 2025)

pH/GSH-Driven inside-out nanoreactor initiating copper(I)-precursor chelation-promoted bioorthogonal therapy - Zhexiang Wang; Xinyi Li; Rui Lv; Ruochen Guo; Qinglei Shu; Tianjin Ge; Jun Yan; Zhihao Zhao; Guanghui Wang; Jian Liu (Chemical Engineering Journal, 2025)

Saline water treatment coupled with carbon dioxide capture by bipolar membrane electrodialysis in a continuous feed-bleed mode: The effect of proton leakage - Tianyi Chen; Ruochen Shen; Hongshuo Sun; Jingtao Bi; Mengmeng Sun; Shizhao Wang; Xiaofu Guo; Wenhao Li; Jianlu Liu; Yingying Zhao (Chemical Engineering Journal, 2024)

Gasification characteristics and sulfur migration mechanism during supercritical water partial oxidation of 2-methylthiophene - Ruochen Xiong; Shi Liu; Jiayi Yu; Zhiwei Ge; Liejin Guo (Chemical Engineering Journal, 2024)

Bipolar membrane electrodialysis integrated with in-situ CO2 absorption for simulated seawater concentrate utilization, carbon storage and production of sodium carbonate - Jingtao Bi; Tianyi Chen; Yue Xie; Ruochen Shen; Bin Li; Mengmeng Sun; Xiaofu Guo; Yingying Zhao (Journal of Environmental Sciences, 2024)

Overlooked in-situ sulfur disproportionation fuels dissimilatory nitrate reduction to ammonium in sulfur-based system: Novel insight of nitrogen recovery - Bo Shao; Li Niu; Yuan-Guo Xie; Ruochen Zhang; Wei Wang; Xijun Xu; Jianxing Sun; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Zheng-Shuang Hua; Chuan Chen (Water Research, 2024)

Genetic and pathogenic characterization of an NADC-34-like isolate of porcine reproductive and respiratory syndrome virus - Yongxin Zhao; Ruiqing Wang; Wei Li; Chenfei Yu; Riteng Zhang; Ruochen Hu; Ruhai Guo; Zengqi Yang; Yefei Zhou; Xinglong Wang (Archives of Virology, 2023)

Analytical method for quantifying performance of wicking geosynthetic stabilized roadway - Wuyu Zhang; Xiongyu Tang; Xiaohui Sun; Ruochen Yang; Guoqing Tong; Jun Guo (Geotextiles and Geomembranes, 2023)

Maximum July–September temperatures derived from tree‐ring densities on the western Loess Plateau, China - Huiming Song; Ruochen Mei; Yu Liu; Daniel Nievergelt; Anne Verstege; Paolo Cherubini; Ruoshi Liu; Changfeng Sun; Qiang Li; Ling Chen; Xueli Zeng; Junqin Guo (International Journal of Climatology, 2021)
Tree‐ring densitometric studies conducted in semi‐arid regions are exceedingly rare. In this study, we evaluate a new maximum latewood density chronology from a collection of Picea purpurea trees growing in semi‐arid northwestern China for climatic reconstruction purposes. We find statistically significant correlations between annual maximum density variations and July–September maximum temperatures over the 1957–2014 calibration period. Using a linear model to transfer the density variations to temperature estimates, we then reconstruct maximum summer temperatures from 1840 to 2014. Statistical analyses and verification tests demonstrate that the resulting transfer function is both reliable and stable. The reconstructed temperature series shows strong inter‐annual and decadal variability. Several extremely cool and warm years are apparent on an inter‐annual scale, while three extended cool periods and a warm period are observed on a decadal scale. In addition, the reconstructed temperature series exhibits a pattern synchronous with that of the Indian monsoon index, as well as a moderate relationship to volcanic eruptions. This densitometric study reveals typical climatic variation characteristics and provides useful data for deepening our understanding of climate history in the semi‐arid regions of China.